Direct current electrocorticography for clinical neuromonitoring of spreading depolarizations. Issue 5 (May 2017) - Hartings, Jed A; Li, Chunyan; Hinzman, Jason M; Shuttleworth, C William; Ernst, Griffin L; Dreier, Jens P; Wilson, J Adam; Andaluz, Norberto; Foreman, Brandon; Carlson, Andrew P
Spreading depolarizations cause cortical electrical potential changes over a wide spectral range that includes slow potentials approaching the direct current (or 0 Hz) level. The negative direct current shift (<0.05 Hz) is an important identifier of cortical depolarization and its duration is a measure of potential tissue injury associated with longer lasting depolarizations. To determine the feasibility of monitoring the full signal bandwidth of spreading depolarizations in patients, we performed subdural electrocorticography using platinum electrode strips and direct current-coupled amplifiers in 27 patients with acute brain injury at two neurosurgical centers. While large baseline direct current offsets developed, loss of data due to amplifier saturation was minimal and rates of baseline drift throughout recordings were generally low. Transient negative direct current shifts of spreading depolarizations were easily recognized and in 306/551 (56%) cases had stereotyped, measurable characteristics. Following a standardized training session, novice scorers achieved a high degree of accuracy and interobserver reliability in identifying depolarizations, suggesting that direct current-coupled recordings can facilitate bedside diagnosis for future trials or clinical decision-making. We conclude that intracranial monitoring of slow potentials can be achieved with platinum electrodes and that unfiltered, direct current-coupled recordings are advantageous for identifying and assessing the impact of spreading depolarizations.